(3GdNWQ hGdJCejfs - (3EHQGgje Ydj EHQGgje(B, (3YHO QHgs ((3GdEScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2008)
(3jVe eaghe GdNWQ, GdJCejf fTCJg hJWhQg hGdJbSjeGJ GdeNJdaI dg hGdeHGOF GdJj jbhe YdjgG hCgejJg, GdJCejf Ydi GdMjGI, GdCbSGW GdhMjOI GdUGajI, GdCbSGW GdSfhjI GdUGajI, GdbSW GdJLGQj, JCejf GdSjGQGJ, GdJCejf Ydi GdMQjb, GdJCejf GdHMQj, EYGOI GdJCejf, GdJCejf GdGLJeGYjs
(3GdeQGLY U(B.527s
Keywords: (3EYGOI GdJCejfs; (3GdJCejf (B- (3GdHfhcs; (3GdJCejf (B- (3GdeNGWQs; (3GdJCejf GdELJeGYj(B- (3GdLRGFQs